(untitled) (Latin-American Journal of Computing, 2017)
In this paper the problem of obtaining the Optimal Workforce Planning for enterprises is addressed as a mathematical optimization problem. Given the complexity and specific features of the corresponding optimization model, the Ant Colony Optimization metaheuristic was applied as the solution method. From computational experiments, we have shown the effectiveness of our proposal versus other state-of-art algorithms.